2019
DOI: 10.1038/s41467-019-11489-y
|View full text |Cite
|
Sign up to set email alerts
|

Programmable four-photon graph states on a silicon chip

Abstract: Future quantum computers require a scalable architecture on a scalable technology—one that supports millions of high-performance components. Measurement-based protocols, using graph states, represent the state of the art in architectures for optical quantum computing. Silicon photonics technology offers enormous scale and proven quantum optical functionality. Here we produce and encode photonic graph states on a mass-manufactured chip, using four on-chip-generated photons. We programmably generate all types of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(71 citation statements)
references
References 45 publications
2
69
0
Order By: Relevance
“…The on-chip GMM of four-photon four-qubit graph states was demonstrated in a Si-chip ( Fig. 4f) [87]. The device includes four waveguide SFWM-SPSs creating two-pairs of photons and a reconfigurable two-qubit linear-optic operator.…”
Section: On-chip Quantum Information Processing With Photonsmentioning
confidence: 99%
“…The on-chip GMM of four-photon four-qubit graph states was demonstrated in a Si-chip ( Fig. 4f) [87]. The device includes four waveguide SFWM-SPSs creating two-pairs of photons and a reconfigurable two-qubit linear-optic operator.…”
Section: On-chip Quantum Information Processing With Photonsmentioning
confidence: 99%
“…Considerable experimental effort [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] is being dedicated to the realization of linear optical quantum computation [19,20] due to the extensive coherence times that photonic qubits promise. To support this endeavor, we must design robust models of fault-tolerant quantum computation that minimize the high resource cost that is demanded by their implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the interference which occurs in the BosonSampling experiments with linear optics, the underlying effect in our crystal network is multiphotonic frustrated photon generation. It would be exciting to see an actual implementation in a laboratory -potentially in integrated platforms which allow for on-chip photon pair generation [61][62][63][64][65][66][67][68]. While we have shown that the expected n-fold coincidence counts will be larger than in conventional Boson-Sampling systems, an important question is how these systems compete under realistic experimental situations.…”
Section: Graphical Description For Quantum Protocolsmentioning
confidence: 92%